La acción educativa como acción narrativa (2009)
ABSTRACT: This article is the result from a theoretical review that defines a perspective about the problem of educational action in classical instrumental pedagogy. According to this pedagogy, the teacher (male or female) is the knowledge transmitter and the student is the receiver. The de-responsibilization of both the teacher and the student with reference to the learning process and the moralization of the educational action are two consequences resulting from this perspective. It proposes that the conception of the human being as a narrative subject helps to find a solution to this problem. The proposal consists of a narratively- based “we” pedagogy that makes possible to construct a different student or teacher’s identity from instrumental pedagogy. The “who am I?” question makes identity construction viable, thus promoting a heteronomous ethics based on the otherness of narrative identity.